Diversity and Inclusion Strategies in Global Organizations: A Systematic Literature Review - Razak, Ikhsan S. Abd (Penelitian dan Pengembangan Ilmu, 2024)
Implementation of Change and Innovation (C&I) strategies in organizations often faces major challenges such as resistance to change, hidden biases, and resource limitations. These challenges can hinder the effectiveness of C&I initiatives and impact organizational outcomes. This research aims to explore the challenges associated with implementing C&I strategies and identify effective approaches to overcome these challenges. Specifically, this research aims to understand how Social Justice Theory can be applied to increase the success of C&I initiatives by mitigating resistance, bias, and resource constraints. This research uses a literature study approach and thematic analysis. Data was collected from a variety of academic and practical sources that address challenges in C&I implementation, social justice theory, and change management techniques. Analysis is carried out to identify relevant patterns and recommendations. The research results show that resistance to change can be reduced through active employee involvement and participation in the decision process. Hidden bias can be minimized with systematic bias awareness training. Resource limitations can be managed by establishing clear and measurable evaluation metrics. Social Justice Theory provides a framework for addressing these challenges by prioritizing principles of justice and inclusion. The implications of this research suggest that to increase the effectiveness of C&I strategies, organizations must integrate social justice principles in their managerial practices. An approach that involves employee engagement, bias training, and the use of clear evaluation metrics can help organizations overcome existing challenges and achieve better results in C&I initiatives. This research provides practical guidance for organizations in designing and implementing more effective C&I strategies.